Taming Variability in T-Cell Mechanosensing - Paula J. Schultheiss; Aarya Pulkundwar; Wangqi Li; Lance C. Kam (Cells)
A central step in T-cell immunotherapy is the expansion of a starting population into therapeutically potent numbers of these “living drugs”. This process can be enhanced by replacing the mechanically stiff materials used for activation with softer counterparts. However, this mechanosensitive expansion response varies between individuals, impeding the full deployment of potential cell immunotherapy. This report identifies the sources of this variability, ultimately improving the reliability of T-cell expansion. T cells from a cohort of healthy donors were phenotypically characterized, activated, and expanded in vitro on soft and hard substrates, capturing and quantifying a wide range of mechanosensing responses. An analysis of expansion against demographic and phenotypic features correlated mechanosensing with the percentage of effector T cells (TEffs) in the starting population. Depletion experiments confirmed that TEffs mediate mechanosensitive expansion but also suggest that these cells are not responsible for large-scale cell production. Instead, population-level expansion results from interactions between T-cell subtypes. By providing a framework and experimental approach to understanding donor variability, the results of this study will improve the success and reliability of T-cell immunotherapy.